Development of kenaf polymer composite sandwich structure - Mohd, Nurul Farah Adibah (2015)
This research presents the development of kenaf polymer composite sandwich structure. The aim of this research is to propose natural fibre composites to be introduced in metal matrix composites material for further manufacturing processes. The core natural fibre material used is kenaf fibre while polyester and polypropylene act as matrix materials. LM6 material was selected as metal matrix composites and used as the skin of sandwich layers for simulation study. Two types of composite processes had been used in this research, hand lay-up process for application of polyester and hot moulding process for polypropylene application. These two types of laminate composite have been tested to analyse the mechanical properties and thermal properties. Based on the testing results, kenaf-polyester composite had been chosen as the proposed material to be applied to the sandwich model. The natural fibre composites were tested by mechanical and thermal testing procedures to meet the ASTM requirements. There were 5 types of ASTM standard has been used in this research such as ASTM D3039, ASTM D638-99, ASTM D7624, ASTM D790 and ASTM E794-01. Tensile test, flexural test, and thermal test had been used in this research. Five specimens were prepared for tensile test and flexural test, followed by one specimen for each laminate composite in thermal test. Thermal test procedure had been prepared by using DSC (Differential Scanning Calorimetric) method. The results showed the polyester was the optimum material to be used as the matrix material for laminate composite due to the high tensile and flexural strength as well as high in the value of maximum force. The DSC test result shows the greater melting temperature in polyester as compared to polypropylene. Furthermore, the LM6 model and sandwich model were designed by using SolidWorks simulation to determine the stress distribution, displacement distribution and factor of safety. As a result, kenaf-fibre polyester composite as core layer in sandwich model of LM6 was potential to be applied for engineering application.